A comparative study of two decoupling control strategies for a coupled tank system - Mahapatro S.R.; Subudhi B.; Ghosh S.; Dworak P. (My University, 2025)
This paper presents a comparative study of two controllers namely Internal Model control (IMC) decoupling controller and an inverted decoupling controller applied to a coupled-tank liquid level system. These controllers are designed based on identified First Order Plus Dead Time (FOPDT) model of a coupled tank system. The performance of the two decoupling controllers are studied considering input and output multiplicative uncertainties. From the simulation and experimental studies, it is found that the inverted decoupling approach is more robust compared to IMC. © 2016 IEEE.